Case report: Ultrasound-guided multi-site electroacupuncture stimulation for a patient with spinal cord injury - Song, Xi-Zi; Chu, Xiao-Lei; Liu, Tao; Cao, Yu-Tong; Li, Rui-Xin; Gao, Ming-Wei; Li, Qing-Wen; Gu, Xiao-Song; Ming, Dong (Frontiers in Neurology, 2022)
Introduction Spinal cord injury causes permanent neurological deficits, which have devastating physical, social, and vocational consequences for patients and their families. Traditional Chinese medicine uses acupuncture to treat neuropathic pain and improve nerve conduction velocity. This treatment can also reduce peripheral nerve injury joint contracture and muscle atrophy in affected patients. And it's got a remarkable restoration when electrical stimulation therapy on impaired peripheral nerves in animal models and clinical trials. Case description A 48-year-old woman was hit by a heavy object that injured her lower back. The patient had a T12-L1 vertebral flexion and stretch fracture with traumatic spinal stenosis. The patient was transferred to the rehabilitation department after posterior T12-L2-segment pedicle screw system distraction and reduction, internal fixation, decompression, and bone graft fusion. Ultrasound-guided electroacupuncture was used to stimulate the sacral nerve, the spinal nerve, and the head of the patient, accompanied by spinal joint loosening training, respiratory training, lumbar comprehensive sports training, paraplegic limbs comprehensive training, and other manipulative treatment. Outcomes After the intervention, the patient showed significant improvements in sensory and motor scores, resulting in functional recovery according to ASIA and FIM. The patient gradually showed reasonable functional remission. Discussion The sacral nerve, the spinal cord, and the head were electrically stimulated by ultrasound-guided electroacupuncture in terms of intervention, and various functions of the patient were alleviated to a certain extent. The efficacy of ultrasound-guided electroacupuncture stimulation in treating neurologic symptoms should be validated in future clinical trials.